BUILDING ASNAF ENTREPRENEURSHIP IN INDONESIA: A PROPOSED PROGRAM FOR AMIL ZAKAT INSTITUTIONS - Dian Friantoro; Muhammad Dzulfaqori Jatnika; Listia Andani; Lu'liyatul Mutmainah; Biki Zulfikri Rahmat (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2022)
Abstract: Currently, the distribution of zakat is usually carried out consumptively to meet the basic needs of mustahiq (zakat recipient). Consumptive zakat provides a short-term effect and a dependency effect for asnaf (mustahiq). Therefore, zakat institutions can begin to develop sustainable productive zakat schemes for the welfare of mustahiq. The research aims to design a program and implementation model for Indonesia’s Asnaf Entrepreneurship Program (AEP). This research uses a qualitative approach with descriptive-analytical methods through literature studies. The AEP program is aimed for asnaf, who meets the criteria of people in need and people experiencing poverty but have the capability to run a bussiness, both physically and mentally. Furthermore, the asnaf are given business assistance by zakat institutions. Assistance can be in the form of a capital loan with a qardh contract, while business assistance can be in the form of consulting, training, and monitoring to achieve a profitable and sustainable business. AEP is implemented using the concept of collaborative management. Several zakat institutions may build an AEP compartment to support AEP applications. Mustahiq also can create a community based on the type of business or place of residence. AEP implementation may be challenging but has potential, not only for the benefit of asnaf but also for its multiplier effect on the Indonesian economy.